China’s Stem Cell Research and Knowledge Levels of Medical Practitioners and Students - Deng Luo; Zihui Xu; Zhongjing Wang; Wenzhuo Ran (Stem Cells International)
Over the last few decades, China has greatly expanded its scope of stem cell research, generating various scientific advances and medical applications. However, knowledge of the extent and characteristics of domestic stem cell development, particularly medical workers’ opinions, is lacking. This study’s purposes were to analyze the growth trends of China’s stem cell community and identify the knowledge and attitudes held by Chinese medical workers regarding stem cell research. We found that there are currently 13 high-quality stem cell research centers with more than 400 PhD-level researchers across Mainland China. These centers feature many high-caliber scientists from the stem cell research community. From 1997 through 2019, the National Natural Science Foundation of China allocated roughly $576 million to 8,050 stem cell programs at Chinese universities and research institutions. China’s annual publications on stem cells increased from less than 0.6% of the world’s total stem cell publications in 1999 to more than 14.1% in 2014. Our survey also revealed that most participants held positive attitudes toward stem cell research, supported further funding, and had high general awareness about stem cells.